Single-Stage Microwave-Assisted Coconut-Shell-Based Activated Carbon for Removal of Dichlorodiphenyltrichloroethane (DDT) from Aqueous Solution: Optimization and Batch Studies - Azrina Aziz; Mohamad Nasran Nasehir Khan; Mohamad Firdaus Mohamad Yusop; Erniza Mohd Johan Jaya; Muhammad Azan Bin Tamar Jaya; Mohd Azmier Ahmad (Hindawi Publishing, 2024)
Indexed by WOS/SCOPUS/ERA